Violência Conjugal no Âmbito Doméstico: as vozes de mulheres que romperam com a agressão - PACHECO, Leonora Rezende (2012)
The conjugal violence against women in the domestic ambient is an internacional problem. It got notoriety since 90 s decade, in several sectors of the society because of their evil consequence and to be an uncompliance of the human rights. The health sector, through their professionals, should compose a multidisciplinary work to prevent this form of violence and give support to an aggrieved woman. The objective of this work is to understand the meaning of conjugal violence for women victims of aggression and to identify factors that contribute to break with this situation in order to give subsidies to nurses provides care for women in this situation . The theoretical reference consist of the definition of conjugal violence in the domestic ambient, the social construction of gender and cultural pillars that sustain gender violence. The methodological reference is of qualitative modality, with Social Research as a methodological procedure used. The study included 05 women victims of conjugal violence, that lives sheltered at the Centro de Valorização da Mulher; were done semi-structured interviews, captured photographies images and observations in the field. The analysis of the results was based on the thematic modality of content analysis, originating three thematic categories: "Living with the Violent Acts", which relates the period that the women lived with the aggressor, being significant the forms of violence perpetrated against them: physical, psychological, sexual and property; "Marks of the Violent Acts", in which women show the marks of violence that stay with her after breaking with the aggressor. This marks are physical, sexual and emotional that affect their health; finally, the third category, "Support to Women", which brings the support that they had or would like to have during the process of breaking with the aggressor. The women express how should be the assistence of the health professional to attend them and the need of this professional in the shelter. The study contributed to understanding the meaning of conjugal violence, with all its specificities, offering subsidies for nurses to provide quality care to these women.